1985
DOI: 10.1016/0014-5793(85)80928-5
|View full text |Cite
|
Sign up to set email alerts
|

Thiophilic adsorption ‐ a new method for protein fractionation

Abstract: Dlvlnyisulphone-activated agarose to which mercaptoethanol IS coupled showed very setectlve group adsorption of human serum protems, m particular the ~mmunogIobul~ns The adsorptxon Increases markedly m the presence of high concentrations of neutral water-structure formmg salts and IS dlstmct from adsorptions based on hydrophobic mteractlon A characterlstlc feature of this new type of adsorbent 1s the structure of the groups attached to the polymer, @, I e , R-S-CH,-CH,-SO,-CH,-cH,-O-Q, where R IS a small ahpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(78 citation statements)
references
References 5 publications
2
73
0
3
Order By: Relevance
“…"Thiophilic-interaction chromatography" (TIC) technique was introduced originally by Porath and his colleagues for the isolation of immunoglobulins [12]. TIC has been used successfully for characterization of human transferring [13], alzheimer's beta-amyloid peptides [14] and for purification of immunoglobulins from chicken sera [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Thiophilic-interaction chromatography" (TIC) technique was introduced originally by Porath and his colleagues for the isolation of immunoglobulins [12]. TIC has been used successfully for characterization of human transferring [13], alzheimer's beta-amyloid peptides [14] and for purification of immunoglobulins from chicken sera [15].…”
Section: Introductionmentioning
confidence: 99%
“…This chromatographic step is based upon salt-promoted adsorption of proteins to the resin, where the binding of proteins to a sulfone and thio-ether-containing hetero-aliphatic ligand takes place mainly through accessible tryptophan and/or phenylalanine residues. The desorption of bound proteins is achieved when the salt concentration is reduced [12]. In our earlier studies, we have shown that PSA and PSA complexes have strong affinity for different thiophilic gels (T-gels), and that T-gel affinity can be successfully applied for the purification of PSA and PSA-complexes from biological fluids, including serum and seminal plasma [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Serum was adjusted to pH 5.5 by adding one volume of 0.5 M sodium acetate (pH 5.5), and it was salted out by adding ammonium sulfate to 1.95 M. After 2 h at room temperature, the supernatant was recovered by centrifugation (4,000 ϫ g for 20 min), and the precipitate was washed with 1.95 M ammonium sulfate. The combined supernatants were dialysed extensively against 1.75 M ammonium sulfate at 4°C and applied to a thiophilic adsorbent (Affi-T agarose; Kem En Tec, Copenhagen) equilibrated in 1.75 M ammonium sulfate (25,26). By using a flow of Ϸ0.5 ml͞min, the adsorbent was washed to its baseline with the same buffer and eluted with 1.5 M ammonium sulfate, followed by 0.1 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Activity of factor II, V, VIII and X was determined with the help of coagulometric methods and Helena BioSciences reagents. Coagulation system ex vivo studies were performed in normal human plasma after addition of lyophilized monoclonal IgG, isolated with the help of thiophilic adsorption method from 20 ml of the patient's blood collected at the time admission [8][9][10]. Thereafter, the activity of factor II, factor V and aPTT, PT and TT in the prepared plasma samples (a series of dilutions of monoclonal IgG in standard human plasma at final concentration of 0, 0.468, 0.937, 1.875, 3.75, 7.5, 15 and 30 g/l, respectively) were measured.…”
Section: Casementioning
confidence: 99%